DISSIMILATION, ASSIMILATION AND THE UNMIXING OF PEOPLES: GERMAN AND CROATIAN SCHOLARS WORKING TOWARDS A NEW ETHNO-POLITICAL ORDER, 1919–1945*. (24th October 2014) - Korb, Alexander
ABSTRACT: This paper deals with a transnational network of scholars and their demographic concepts of ethnic homogenisation of Europe. Focusing on the ethnographer Karl Christian von Loesch and the sociologist Max Hildebert Boehm, it sheds light on German supremacist scholarship and its international entanglements in the interwar years. Loesch and Boehm headed the Institute for Borderland and Foreign Studies in Berlin, where they developed concepts of a new European demographic order based on ethnic segregation, border shifts, assimilation and population transfers. They closely cooperated with non-German nationalists. Indeed, Loesch and Boehm had a big impact on non-Germans scholars, who studied at their institute and who would later try to apply similar concepts of ethnic homogenisation to their countries. By discussing the work of three of their students, Franz Ronneberger, Mladen Lorković and Fritz Valjavec, the paper presents a case of transnational cooperation between German and south-eastern European scholars. Using Croatia as an example, the paper demonstrates how these scholars worked towards nation-states freed of ethnic minorities. The Second World War would bring them into a position to try to implement their projects. Yet, the brutal dynamics of the war quickly altered the reality scholars had planned to design. The grand demographic schemes paved the way for ethnic cleansing, but had not much to do with the way they were carried out.